A scenario-based methodology for determining fire resistance ratings of irregular steel structures. Issue 1 (January 2020) - Behnam, Behrouz
This article investigates the response of irregular steel structures under natural fires. As the severity and duration of natural fires depend on many factors, a probabilistic-based approach known as two-level factorial design is used, whereby possible fire scenarios are considered based on the minimum and maximum values of the involved factors. Two seven-story regular steel structures with three span lengths of 5500 and 7000 mm are designed to meet a 2.0-hr fire resistance rating based on the ISO834 fire. Two types of irregularities, setback and soft story, are then imposed on the regular structures to make them irregular. The regular and irregular structures are then exposed to the fire scenarios (32 in total) to evaluate their fire resistance ratings. The results show that while the regular structures are able to meet the required fire resistance rating under all of the fire scenarios, this is not the case for the irregular structures. It is shown that the reduction in the fire resistance ratings of the setback and the soft-story structures can be as low as 45% and 33% that of the required fire resistance ratings, respectively. Also, the setback irregular structures tend to collapse laterally, hence endangering the safety of adjacent buildings. To address the above deficiencies, it is proposed here that the maximum surface temperature on the structural members should be limited to 415°C–460°C. Alternatively, providing a 20%–25% increase in the insulation thickness can provide the required safety margin as dictated by fire codes.